Optimalisasi Pelayanan Perpustakaan Sebagai Upaya Pemberdayaan Masyarakat Untuk Meningkatkan Literasi Anak Di Desa Pulau Terap, Kecamatan Kuok, Kabupaten Kampar, Provinsi Riau - Suyanto, Suyanto; Erliansyah, Mhd. Daffa; Wahyudi, M. Irfan; Fazikri, Heldi; Nurhayati, Naura; Rahmadani, Oki; Nasaf, Nabil Al; Aprialini, Muthia Hidayah; Salsabila, Aurenia; Hasanah, Layla Tillawatil; Putri, Dwita Puspa Oktaviani; Anisa, Syafira (Unri Conference Series: Community Engagement, 2025)
The low reading interest among children in Pulau Terap Village, Kuok District, Kampar Regency is caused by limited competence of library managers, minimal community participation, and lack of adequate programs and facilities. This activity aims to optimize Perpustakaan Cerdas Abadi services through community empowerment to improve children's literacy. Qualitative methods were used through observation, interviews with library managers, community leaders, parents, children, and activity documentation. Empowerment was conducted in stages including community awareness, manager capacity training, and literacy program implementation. Three innovative programs were implemented: "Read Aloud", "Literacy Visits" to five schools, and "National Children's Day Commemoration" with educational competitions. The program involved collaboration between village government, community leaders, and parents. Results showed increased children's enthusiasm and participation, community awareness about literacy importance, increased library visits, and strengthened community social bonds through sustainable literacy programs.